Dual practice of public hospital medical doctors at county referral hospitals in Nairobi, Kenya - Karugu, Lucy (Strathmore University, 2021)
This study assessed the dual practice of public hospital medical doctors at county referral hospitals in Nairobi, Kenya. The three-county referral hospitals under investigation were Pumwani hospital, Mbagathi hospital, and Mama Lucy hospital. Specifically, the study aimed to 1) establish the prevalence or extent of the dual practice of public hospital medical doctors; 2) determine forms and/or modes of dual practice of public hospital medical doctors; 3) identify factors that drive the dual practice of public hospital medical doctors; 4) find out reasons for commitment to public practice among public hospital medical doctors; and 5) examine consequences or impacts of dual practice of public hospital medical doctors. This study achieved these objectives through mixed methods of data collection and analysis. Moreover, the study adopted a descriptive online questionnaire survey with semi-structured and open-ended questions to collect data from 63 respondents (38 – medical doctors and 25 management teams) across the three hospitals under investigation. The Census sampling technique was adopted. The findings reported that the prevalence or extent of the dual practice of public hospital medical doctors is at 54%. Most public hospital medical doctors who engage in dual practice do so because of the low/negative perception they have on their current public practice income. The findings also indicate that the motivating factor or reason why most public hospital medical doctors engage in dual practice is to enhance their current income. That is to say, private practice income supplements public practice income. Though there exist dual practices among some public hospital medical doctors, the study established that some public hospital medical doctors, however, are committed to public practice. Results indicate that the responsibility to uphold public health for all and building reputation are some of the reasons some public hospital medical doctors are committed to public practice. Also, the study found out that faster promotion, increased salary, and provision of housing benefits are some of the conditions that would make the majority of the public hospital medical doctors who engage in dual practice give up their private practice for public practice. Consequently, the study findings report that consequences of the dual practice of public hospitals medical doctors varies and can either be positive or negative to the health system, patients, and public health institution. This study concludes that healthcare remains a development priority across nations. As the demand for health services increases so will the dual practice of public hospital medical doctors due to the growing disparity in the doctor-patient ratio. The study recommends the need for more policy frameworks on dual practice to work for the benefits of public hospitals. Also, the study recommends further research to focus on all county referral hospitals in Kenya with large sample size.
A Dissertation submitted in partial fulfillment of the requirements for the award of the Degree of Master of Business Administration in Healthcare Management at Strathmore University
Keywords: Dual practice; Public hospital medical doctors; County referral hospitals